(untitled) (Global Journal of Human-Social Science, 2014)
Al Mahmud explores Muslim history for imagery and effectively uses them in his poetry to speak for suppressed humanity in different corner of the world and to protest against the oppressors of humanity. His poetry inspired by Islamic spirit pungently protests against tyrants of the world. He resists imperialistic evil oppressors through Islamic spirit in his rebellious poetry. Islam inspires its followers to abolish all kinds of injustice from earth and to establish parity and peace on earth. He is greatly inspired by the spirit of jihad in Islam to accomplice this task. He regards jihad as the last step to abolish evil as well as a means of self defence. He has also glorified prayer by raising it to the most consecrated level infusing the spirit of jihad in it and upheld the high ideals of humanity of Islam. He sings to restore the rights of all mankind on earth and Islamic spirit adds an extra dimension to his song. His poetic diction from rural Muslim world raises his poetry to an extra-ordinary level.